Health insurance coverage and its associated factors amongst households of an urban village in Delhi - Suraj P. Singh; Anita Khokhar (Journal of Family Medicine and Primary Care, 2025)
Context: Urban poor households mostly comprising of migrants from small towns and villages are prone to residing in overcrowded, unplanned settlements, bearing a higher risk of healthcare ailments and expenditure. There is a need to assess health insurance amongst them to better understand insurance coverage, as well as their experience and attitude towards it. Aims: To find out the prevalence of health insurance and its associated factors amongst households of an urban village in Delhi. Settings and Design: A cross-sectional study amongst households that have been residing for the last year in an urban village of Delhi. Methods and Material: This 18-month duration study was carried out in an urban village of Delhi, where a sample size of 188 was calculated based on a study conducted in Dakshina Kannada, and households were selected using systematic random sampling. A pre-designed, pre-tested, semi-structured, and interviewer-administered questionnaire was used in Hindi to elicit and record relevant information. Statistical analysis used: Data was recorded and coded in MS Excel, and analysis was done using licensed IBM SPSS v. 26. Tables were generated for relevant data, and cross-tables were used to assess statistical association with Chi-square or Fisher’s Exact tests, as required. Multivariate logistic regression was applied to the variables found to have a statistically significant association in cross-tables (P < 0.05). Results: Almost sixty percent of study households had no health insurance coverage, while 39.4% of households had some degree of health insurance, and only 53 (28.2%) had complete health insurance coverage of all household members. Conclusions: Only 28.2% of households in the urban village of Aliganj, Delhi, are covered under health insurance.